1975
DOI: 10.3109/00016347509157104
|View full text |Cite
|
Sign up to set email alerts
|

Studies in Cholestasis of Pregnancy

Abstract: Women from an earlier series of cholestasis of pregnancy (CP) were called for a retrospective study to consider presence of gallstones in the gallbladder (evaluated by cholecystography), liver function tests, serum lipids and lipoproteins and the relative fatty acid composition of serum lecithin (as determined by GLC). The attendance in the retrospective study was 60%. Estimated on the total series (assuming that none of the non-responders would have a positive X-ray), the incidence of gallbladder disease was … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
3
0

Year Published

1982
1982
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(4 citation statements)
references
References 21 publications
1
3
0
Order By: Relevance
“…This supports the current view of multiple pregnancy being a risk factor for ICP [3]. In addition, ICP is associated with a predisposition for cholesterol gallstones, and there is an increased incidence of ICP among gallstone patients [27,28]. The study by Savander detected a 22 % prevalence of cholelithiasis in ICP patients.…”
Section: Course Of Disease and Prognosissupporting
confidence: 72%
“…This supports the current view of multiple pregnancy being a risk factor for ICP [3]. In addition, ICP is associated with a predisposition for cholesterol gallstones, and there is an increased incidence of ICP among gallstone patients [27,28]. The study by Savander detected a 22 % prevalence of cholelithiasis in ICP patients.…”
Section: Course Of Disease and Prognosissupporting
confidence: 72%
“…The disruption of normal bile salt function can impair fat malabsorption and vitamin K absorption resulting steatorrhea and prolonged prothrombin time may risk for postpartum hemorrhage. 39 ICP also associates with gallbladder stone, 40 and post cholecystectomy. Ultrasonography confirms diagnosis.…”
Section: Clinical Featuresmentioning
confidence: 97%
“…Women with ICP have an increased risk of cholesterol gallstones in later life (8). A recent study from Finland showed an association between ICP and several liver and biliary diseases (9).…”
Section: Introductionmentioning
confidence: 99%